Case Report: Management of a Patient With Chylomicronemia Syndrome During Pregnancy With Medical Nutrition Therapy - Zahedi, Maryam; Asghari, Golaleh; Mirmiran, Parvin; Hosseinpanah, Farhad (Frontiers in Nutrition, 2021)
Background: Hypertriglyceridemia (HTG) during pregnancy may be accompanied by acute pancreatitis, hyperviscosity syndrome, and preeclampsia. HTG during pregnancy should be managed by a multidisciplinary team; however, no clinical guidelines exist for severe gestational HTG. Case presentation: We herein present a case of a 36-year-old, with the first pregnancy (G1P0Ab0) and a history of severe HTG-induced necrotizing pancreatitis 9 years earlier. There was no family history of HTG. During these years, she did not follow any appropriate diet or medical therapy for HTG. She became pregnant in May 2019, without preconception counseling. Eruptive and tuberoeruptive xanthomas appeared in the 27th week of pregnancy. Serum triglycerides (TGs) and fasting blood sugar (FBS) were 6620 and 124 mg/dL, respectively, indicating HTG and gestational diabetes (GDM). After admission for the management of severe HTG, she was put on parenteral nutrition with dextrose water 5% and infusion insulin therapy without receiving any enteral carbohydrate for two days. Following that, a very low-fat diet and omega-3 fatty acids (1200 mg/day) were stated. After 4 weeks, TG levels reached 1000 mg/dL, and her self-monitoring blood glucose levels showed appropriate blood glucose for pregnancy. She underwent a successful elective cesarean section in the 39th of pregnancy. Conclusion: This case report demonstrates that HTG during pregnancy could be managed by medical nutrition therapy (MNT).